The friendship as a way of resistance: reflections about Amista' (2021) circus play (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The following work sought to develop a series of analyzes and reflections based on the circus play Amista' (2021) by Tomi Soko, in which the intimate and affective relationship of three traffic light jugglers unfolds. It was interesting to think about the political decision to create from that starting point, since tensions over money, competition between street artists and the dispute for recognition are exposed during the work. The article was structured in three axes where the political acquires specific connotations: the theme, the language and the creative process; perspectives that in turn feed each other. Doing the reverse path to the staging, we started from the visible result to delve into the initial investigation process of the work, putting in the center the question about the relationship between the bodily knowledge of the traffic light jugglers and the aforementioned axes.
Keywords: Circus; Street art; Political art; Body